Midwifery Students' Experiences in Learning Pelvic Anatomy and Childbirth Mechanisms: A Phenomenological Study - Nelly, Nelly Karlinah; Irianti, Berliana; Maita, Liva; Sari, Ria Harnita; Israyati, Nur; Setiawati, Sandy; Ridha, Muhammad (Indonesian Socety of Obstetrics and Gynecology, 2025)
Objectives: To determine students' competence in pelvic anatomy and labor mechanisms through multimedia-based learning media at University Hangtuah Pekanbaru and Helvetia Health Institute Pekanbaru Methods: The design of this study is a qualitative study with a descriptive phenomenological approach using the framework standards for reporting qualitative research a synthesis of recommendations approach. The number of informants in this study was 10 people, consisting of 8 midwifery students, 2 lecturers. Recruitment of informants in this study used purposive sampling. Analysis of research data using the Collaizi's framework, namely first familiarization, identifying related statements, formulating meaning, grouping themes, developing in-depth descriptions, creating basic structures of statements and final validation. Results: The results of the analysis obtained two themes, namely the parts of the pelvic bone and the process of childbirth. Informants revealed that during the learning process they got a method of the process of childbirth so that it made it easier for students to practice in the field Conclusion: Learning methods can be accessed not only during learning but also when outside the classroom or in the field Keywords: Pelvic Anatomy, Labor Mechanism, Midwifery Curriculum, Learning Media, Multimedia